The design and development of online authentic learning environment for knowledge construction in learning inferential statistics - Lau, U. H. (Academic Research Publishing Group, 2019)
One of the major problems in learning statistics is due to the learning decontextualized from the real world experience. The students are unable to apply statistical knowledge learnt in real world upon completion of the course. The authentic learning is viewed as a favourable approach in statistics delivery to overcome the problem. However, implementing authentic learning in online platform can be extremely resource intensive and costly to develop. Therefore this paper looked into an innovative and cost effective approach to incorporate the nine critical characteristics of Authentic Learning Model by Herrington and Oliver (2000), underpinned by Vygotsky (1978) Social Development Theory and Lave and Wenger (1991) Situated Learning Theory to develop an online authentic learning environment (OnALE) that foster students' knowledge construction in learning inferential statistics among non-statistics major undergraduates. This environment is established in a social learning network, Edmodo by incorporating Web 2.0 technologies. Perception survey done indicates that OnALE assisted students learning.